Little Seal Finds a Friend - Harris, Sue; illustrated by Boey, Stephanie (Dorking Templar, 2007)
A cuddly harp seal is growing up, happily making mischief with his two best friends$1 (Ba stout baby walrus and a snuggly polar bear cub$1 (Band exploring his Arctic home. One day, mother says it is time to migrate for the season. But the little seal doesn$1 (Bt want to leave! As the herd travels farther and farther south, the pup slips away and heads for home. Can the brave little seal find his way all alone?s
Includes Colored Ilustrarions
Keywords: Seals (Animals) -- Pictorial works -- Juvenile fiction